Fucoidans from South African brown seaweeds: establishing the link between their structure and biological properties (anti-diabetic and anti-cancer activities) - Mabate, Blessing (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Type 2 diabetes mellitus (T2DM) and cancer are major non-communicable diseases causing a heavy morbidity-mortality and economic burden globally. The therapeutic efforts in managing these diseases are primarily chemotherapeutic and are associated with demerits, including side effects and toxicity, limiting the prescribed amounts. These dosage limits may cause drug resistance, another major challenge in maintaining quality global health. The pursuit of novel natural bioproducts is a reasonable strategy to add to the arsenal against T2DM and cancer. Fucoidans, sulphated fucose polysaccharides abundant in brown seaweeds, have recently become popular for their biological activities, including anti-diabetic and anti-cancer properties. However, endemic South African brown seaweeds have not been adequately explored. Therefore, this study sought to characterise fucoidans extracted from South African brown seaweeds and elucidate their structure to their biological activities. Also, this study highlighted carbohydrate and glucose metabolism as major target processes in the control efforts of T2DM and cancer using fucoidans. Harvested brown seaweeds were identified as Ecklonia radiata and Sargassum elegans. E. maxima was kindly donated by KelpX. The fucoidans were then extracted using hot water, EDTA assisted, and acid extraction protocols. The integrity of the extracted fucoidan was confirmed through structural analysis using FTIR, NMR and TGA. The fucoidan extracts were then chemically characterised to determine their carbohydrate and monosaccharide composition and sulphate content. The characterised fucoidans were profiled for inhibiting the major amylolytic enzymes, namely Î±-amylase and Î±-glucosidase. The mode of inhibition by fucoidans and synergy experiments with the commercial anti-diabetic drug acarbose were also investigated. Furthermore, the fucoidans were screened for potential anti-cancer activities on the human colorectal HCT116 cancer cell line. The cytotoxicity of fucoidans was quantified using the resazurin assay. The effect of fucoidan on HCT116 cell adhesion on the tissue culture plastic was also investigated using the crystal violet-based cell adhesion assay. In addition, cancer antimigration properties of fucoidans were also investigated using 2D wound healing and 3D spheroid-based assays. Furthermore, the long-term survival of HCT116 cells was investigated through the clonogenic assay after treatment with fucoidans. Lastly, glucose uptake and lactate export assays revealed the influence of fucoidan on glucose uptake and the glycolytic flux of HCT116 cells. Fucoidans were successfully extracted with a yield between 2.2% and 14.2% on a dry weight basis. EDTA extracts produced the highest yields than the water and the acid extracts. Ecklonia spp. fucoidans displayed the highest total carbohydrate content, with glucose and galactose being the major monosaccharides. S. elegans and commercial Fucus vesiculosus had lower carbohydrate contents but contained more sulphates than the Ecklonia spp. fucoidans. Furthermore, the extracted fucoidan contained little to no contaminants, including proteins, phenolics and uronic acids. In addition, the extracted fucoidans were determined to be >100 kDa through ultracentrifugation. Mass spectrometry also detected the most abundant peak for all fucoidans to be around 700 Da (m/z). Extracted fucoidans inhibited the activity of Î±-glucosidase more strongly than the commercial anti-diabetic agent acarbose but were inactive on Î±-amylase. Fucoidans were also shown to be mixed inhibitors of Î±-glucosidase. Compellingly, fucoidans synergistically inhibited Î±-glucosidase in combination with the anti-diabetic agent acarbose, highlighting prospects for combination therapy. Finally, fucoidans demonstrated some anti-proliferative characteristics on HCT116 cancer cells by inhibiting their ability to adhere to the tissue culture plate matrix. Furthermore, some fucoidan extracts inhibited the migration of HCT116 cancer cells from 3D spheroids. Some of our fucoidan extracts also inhibited HCT116 colony formation, demonstrating inhibition of long-term cell survival. The E. maxima water extract also inhibited glucose uptake by HCT116 cells, thereby influencing the glycolytic flux. In conclusion, biologically active fucoidans were successfully extracted from South African brown seaweeds. These fucoidans demonstrated anti-diabetic and anti-cancer properties, revealing their relevance as potential drugs for these diseases.
Keywords: Fucoidan; Diabetes -- Treatment; Cancer -- Treatment; Brown algae